PEMBERDAYAAN PEREMPUAN MELALUI KOPERASI - Rahma, Sri (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2022)
This study aims to explore the role of cooperatives in women's empowerment in Jambi villages, especially in improving skills, contribution to the family economy, participation in decision-making, and social impact. Through a qualitative approach with interview, observation, and documentation methods, it was found that cooperatives play a significant role in providing skills training, access to business capital, and increasing women's involvement in decision-making. In addition, cooperatives also contribute to a positive change in people's perception of women's roles and increase their confidence and social role. These findings confirm that cooperatives can be an effective model for women's empowerment and community development in rural areas. However, sustained efforts are needed to address social and cultural barriers and ensure adequate support for the sustainability of women's empowerment programs through cooperatives